Crystal Growth of Quantum Magnets in the Rare-Earth Pyrosilicate Family R2Si2O7 (R = Yb, Er) Using the Optical Floating Zone Method - Harikrishnan S. Nair; Tim DeLazzer; Tim Reeder; Antony Sikorski; Gavin Hester; Kate A. Ross (Crystals, 2019)
We report on the crystal growth of rare-earth pyrosilicates, <semantics> R 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> for R = Yb and Er using the optical floating zone method. The grown crystals comprise members from the family of pyrosilicates where the rare-earth atoms form a distorted honeycomb lattice. C-Yb <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> is a quantum dimer magnet with field-induced long range magnetic order, while D-Er <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> is an Ising-type antiferromagnet. Both growths resulted in multi-crystal boules, with cracks forming between the different crystal orientations. The Yb <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> crystals form the C-type rare-earth pyrosilicate structure with space group <semantics> C 2 / m </semantics> and are colorless and transparent or milky white, whereas the Er-variant is D-type, <semantics> P 2 1 / b </semantics> , and has a pink hue originating from Er <semantics> 3 +</semantics>. The crystal structures of the grown single crystals were confirmed through a Rietveld analysis of the powder X-ray diffraction patterns from pulverized crystals. The specific heat of both C-Yb <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> and D-Er <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> measured down to 50 mK indicated a phase transition at <semantics> T N ≈ </semantics> 1.8 K for D-Er <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> and a broad Schottky-type feature with a sharp anomaly at 250 mK in an applied magnetic field of 0.8T along the c-axis in the case of C-Yb <semantics> 2</semantics>Si <semantics> 2</semantics>O <semantics> 7 </semantics> .